The Factors That Support The Success Of Medical Tourism In Malaysia - Tiara Turai; Rita Srihasnita Rosali Caniago; Puti Embun Sari (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2023)
The purpose of this study is to find the factors that supported the success of medical tourism in Malaysia. This study is a conceptual paper that reviews the literature from previous studies that have relevance to the factors that support the success of medical tourism in Malaysia. The factors such as healthcare quality, hospital ‘s brand image, cost competitiveness, government involvement, country knowledge (safe and security, accessibility, price reasonableness) and social aspects factors (word of mouth communication, user generated social media), medical expertise, cultural adaptability, accessibility are the factors that determine the success of medical tourism. At the end of this paper, the author discussed the findings, conclusion, and recommendations for future research ABSTRAK Tujuan dari pembuatan artikel ini adalah untuk menemukan faktor-faktor yang mendukung kesuksesan dari medical tourism di Malaysia. Kajian ini dalam bentuk artikel konsepsual dimana penulis melakukan review dari kajian kajian penulisan terdahulu yang terkait dengan faktor faktor yang mendukung keberhasilan medical tourism di Malaysia. Faktor-faktor seperti kualitas pelayanan Kesehatan, brand image daripada rumah sakit, biaya yang kompetitive, keikutsertaan pemerintah, pengetahuan akan negara dan aspek social, dan kemampuan beradaptasi terhadap budaya merupakan faktor faktor yang menentukan keberhasilan dari pada medical tourism. Diakhir artikel ini, penulis melakukan diskusi akan penemuan peneman, merangkum dan memberikan rekomendasi untuk penelitian mendatang